Patient with Familial Nonsyndromic Cleft Lip and Palate with Unaffected Parents - Demiröz, Anıl; Yıldız Değer, Tuğba Feryal; Suleymanov, Shamil; Aydın, Yağmur; Yıldırım, İbrahim (Cerrahpaşa Medical Journal, 2019)
Cleft lip and palate represents a group of malformations with multifactorial etiology. Here, its etiology has been reviewed in light of the current literature with the presentation of a case of familial nonsyndromic cleft lip and palate. We present the case of one of the dizygotic twins with cleft lip and palate who applied for our clinic in November 2011. 1 year old female patient presented with bilateral primary and secondary complete cleft lip and palate. The other twin brother and 11-year-old sibling underwent cleft lip repair surgery with the same diagnosis in another clinic. Parents and other family members were unaffected. Cleft lip and palate is the most common craniofacial congenital deformity and is associated with multifactorial etiology. The family must be informed about the familial patterns of inheritance and probability of occurrence in subsequent offsprings. Cite this article as: Demiröz A, Yıldız Değer TF, Suleymanov S, Aydın Y, Yıldırım İ. Patient with Familial Nonsyndromic Cleft Lip and Palate with Unaffected Parents. Cerrahpasa Med J 2019; 43(3): 97-101.